Psychotherapy and Social Change: Utilizing Principles of Cognitive-Behavioral Therapy to Help Develop New Prejudice-Reduction Interventions - Birtel, Michèle D.; Crisp, Richard J. (Frontiers in Psychology, 2015)
We propose that key concepts from clinical psychotherapy can inform science-based initiatives aimed at building tolerance and community cohesion. Commonalities in social and clinical psychology are identified regarding 1) distorted thinking (intergroup bias and cognitive bias), 2) stress and coping (at intergroup level and intrapersonal level), and 3) anxiety (intergroup anxiety and pathological anxiety). On this basis we introduce a new cognitive-behavioral model of social change (CBM-SC). Mental imagery is the conceptual point of synthesis, and anxiety is at the core, through which new treatment-based approaches to reducing prejudice can be developed. More generally, we argue that this integration is illustrative of broader potential for cross-disciplinary integration in the social and clinical sciences, and has the potential to open up new possibilities and opportunities for both disciplines.